Напишите решение: : 1) выражение: (7-2x--2)(x+3); (3m^2+3n^2) -(2m+n)(m+2n); u(u+-1)(u-1). 2)преобразуйте в многочлен: (x^2+1)(x^2+2); (3+b^3)(b^3-4); (a^2-b^2)(a-b)^-этот знак означает степень. ,

    1   01.06.2019 01:50    3

Ответы
Попова1234 Попова1234  02.07.2020 11:14
1)7-2x-x^2)-(x-2)(x+3)=7-2x-x^2-x^2-x+6=-2x^2-3x+13
2)(3m^2+3n^2)-(2m+n)(m+2n)=3m^2+3n^2-2m^2-5mn-2n^2=m^2-5mn+n^2
3)u(u+v)-(v-1)(u-1)=u^2++uv-uv+v+u-1=u^2+v+u-1
4)x^2+1)(x^2+2)=x^4+2x^2+x^2+2=x^4+3x^2+2
5)3+b^3)(b^3-4)=3b^3-12+b^6-4b^3=b^6-b^3-12
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра